Meningkatkan Hasil Belajar Siswa Melalui Model Problem Based Learning Dalam Pembelajaran PAI dan Budi Pekerti di SDN 07 Bahagia Panti - Suhaidar, Suhaidar (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to improve students’ learning outcomes in Islamic Religious Education by using the Problem-Based Learning (PBL) model in grade IV of SD Negeri 07 Bahagia Panti. The research was conducted in two cycles, each consisting of planning, implementation, evaluation, and reflection. The results of the study showed that in Cycle I, 52.38% of students achieved learning completeness, while in Cycle II, the percentage of students who completed their learning increased to 85.71%. The implementation of the PBL model was proven to be effective in improving student activity, discussion skills, and understanding of the material. Based on these results, it can be concluded that the use of the PBL model can enhance students’ learning outcomes in Islamic Religious Education.